Climate change law and policy EU and US approaches - Carlarne, Cinnamon P. (Oxford : Oxford University Press, 2010)
This text provides a comparative, socio-legal analysis of global climate change laws and policies in the European Union and the United States, shedding light on the disparate legal and political strategies being used to address climate change in these two regions and the likely successes and failures of current policy strategies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Climatic changes -- Law and legislation -- European Union countries; Climatic changes -- Law and legislation -- United States; Climatic changes -- Government policy -- European Union countries; Climatic changes -- Government policy -- United States